Outcomes in dogs undergoing surgical stabilization and non-stereotactic radiation therapy for axial and appendicular bone tumors - Griffin, Maureen A.; Mastorakis, Andrea; Wustefeld-Janssens, Brandan; Martin, Tiffany Wormhoudt; Duda, Lili; Seguin, Bernard; Tremolada, Giovanni (Frontiers in Veterinary Science, 2024)
Information on dogs that undergo radiation therapy with non-stereotactic protocols in addition to surgical stabilization with implant placement for treatment of bone tumors is limited. Our primary objectives were to describe the clinical characteristics as well as outcomes, including complications, function, and disease progression, in dogs that underwent both surgical stabilization with implant placement and non-stereotactic RT for local treatment of a bone tumor. A bi-institutional retrospective case series was performed, and 8 dogs were included. Tumor types included osteosarcoma or suspected osteosarcoma, plasma cell tumor, and grade 3 fibrosarcoma. Radiation protocols were hypofractionated (palliative intent) in 5 dogs and fractionated (definitive intent) in 3 dogs. Five dogs experienced complications following both RT and surgery, including grade 1 complications in two dogs, a grade 2 complication in one dog, both grade 1 and 2 complications in one dog, and both grade 2 and 3 complications in one dog. Clinical signs subjectively improved in all dogs that had outcomes relative to function documented post-surgery/RT. Of these 7 dogs, 4 maintained long-term improvement in function and clinical signs, whereas 3 experienced subsequent recurrence/progression of clinical signs at a median of 133 days (range 91-186) postoperatively in association with biomechanical complications (screw loosening), surgical site infection, and local disease progression in 1 dog each; subsequent treatment resulted in improved clinical signs for each of these 3 dogs, such that overall good long-term functional outcomes were experienced. No dogs required amputation or additional vertebral surgery as salvage for local disease control or palliation. The median progression free interval was 206 days (range 25-1078), and the median survival time was 253 days (range 122-1078) with 1 additional dog lost to follow-up at 575 days. Two dogs experienced local disease progression, and 6 dogs experienced systemic disease progression; both dogs that developed local disease progression received palliative intent RT protocols. In this cohort, dogs with primary bone tumors that underwent surgical stabilization with implant placement and hypofractionated or fractionated non-stereotactic RT for local treatment had a low incidence of major complications, good limb function and ambulation post-treatment, and relatively prolonged survival times despite disease progression.